A Note So High Nobody Can Reach It: White Supremacy, Citizenship, and Massachusetts' Question 2. - Spooner, Emily J. (Tufts Archival Research Center, 2005)
This paper examines the ways in which larger constructions of citizenship enter into debates about schooling. Specifically, it argues that citizenship transcends its traditional legal definition, and that full citizenship includes the ability to meaningfully participate in American social and legal institutions. This definition of full citizenship, however, has been unevenly distributed on the basis of race, and has therefore led to a conflation of whiteness with citizenship that continues to have pervasive implications for educational policy. This paper uses Massachusetts' Question 2, a 2002 ballot question that mandated English immersion for English language learners (ELLs), as a lens through which to view issues of citizenship and the racial and linguistic construction of Latinos in the United States. In examining Question 2 and the debates surrounding it, this paper suggests that this ballot initiative did not exist in isolation, but entered into a growing racialized anti-immigrant, particularly anti-Latino, sentiment. As a result, this paper uses critical race theory to examine these debates and argues that ultimately, Question 2 and the arguments surrounding it demonstrated a commitment to white supremacy and a failure to recognize the racialized nature of instruction for ELL students.